Patients' views can improve clinical trials for participants. (7th April 2016) - Chauhan, Cynthia; ,
Abstract : Participation in clinical trials is more likely, and the evidence gleaned more useful, when researchers take patients' views into account, writes the patient Cynthia Chauhan